EFFECT OF INJURY PREVENTION TRAINING ON KNEE MECHANICS IN FEMALE ADOLESCENTS DURING PUBERTY. Issue 7 (11th March 2014) - Otsuki, R; Kuramochi, R; Fukubayashi, T
Abstract : Background: Female adolescents change their landing mechanics during puberty. It is unknown whether implementation of anterior cruciate ligament (ACL) injury prevention training reduces the loss of knee control in female athletes during puberty. Objective: To evaluate the effect of injury prevention training on knee mechanics in female athletes during puberty. Design: Controlled before-and-after study. Setting: Youth sports. Participants: 60 female junior high school basketball players participated and were divided into 2 groups: training group (n=32) and control group (n=28). Interventions: The training group underwent an injury prevention program three times per week for 6 months. The focus of the program was to ensure proper movement patterns, particularly avoiding knee valgus motion and encouraging knee flexion. The program was 20 min long and was implemented as a warm-up routine. The control group maintained a regular training routine. Main outcome measurements: The knee valgus motion and knee flexion range of motion during a drop vertical jump were measured before and after the training period. The probability of a high knee abduction moment (pKAM) was also evaluated using an ACL injury prediction algorithm. Results: The knee valgus motion was significantly increased in the control group (P<.001), whereas it did not change in the training group (P=.64). Similarly, the knee flexion range of motion was significantly decreased in the control group (P<.001), whereas it was not changed in the training group (P=.55). The pKAM was significantly increased in the control group (P<.001), but not in the training group (P=.06). Conclusions: Implementation of injury prevention training was effective in limiting the loss of knee control in female athletes during puberty. Although a significant improvement in landing mechanics might not be possible, implementation of injury prevention training should be initiated during puberty to reduce the risk of ACL injury.